Liquidity Traps with Global Taylor Rules - Stephanie Schmitt-Grohe; Martin Uribe (Rutgers University, Department of Economics, 2000)
A key result of a recent literature that focuses on the global consequences of Taylor-type interest rate feedback rules is that such rules in combination with the zero bound on nominal interest rates can lead to unintended liquidity traps. An immediate question posed by this result is whether the government could avoid liquidity traps by ignoring the zero bound, that is, by threatening to set the nominal interest rate at a negative value should the inflation rate fall below a certain threshold. This paper shows that even if the government could credibly commit to setting the interest rate at a negative value, self-fulfilling liquidity traps can still emerge. That is, deflationary equilibria originating arbitrarily near the intended equilibrium and leading to low (possibly zero) interest rates and low (and possibly negative) rates of inflation cannot be ruled out by lifting the zero bound on the monetary policy rule. This result obtains in models with flexible and sticky prices and under continuous and discrete time.
Keywords: E31; E52; E63; 330; liquidity traps; Taylor rules; zero bound on nominal interest rates